Experimental testing and numerical analysis of 3D steel frame system under column loss. (15th April 2016) - Dinu, Florea; Marginean, Ioan; Dubina, Dan; Petran, Ioan
Highlights: Redistribution capacity and development of catenary action in case of column loss were assessed experimentally. Robust moment connections allow development of catenary forces in beams and improve robustness. Two-way frame system enhances redistribution capacity over planar systems as loading demand on each element reduces. Applied element method was used to validate numerical model. Abstract: Multistory steel frames are expected to provide resistance to progressive collapse following local damage or failure caused by extreme loading events. Features like ductility and continuity provide more deformation capacity and redistribution of loads so that the structure can bridge over damaged elements. Special measures should be taken to ensure that the connections can withstand the extreme loading and deformation demands arising from the occurrence of local failure. In addition, two-way frames will enhance the progressive collapse resistance over planar systems as the loading demand on each element reduces. In this study, we investigated the response of two-way steel frame systems under the removal of a central column. Extended end-plate bolted connections were used to join the beams to the columns. First, an experimental test was carried out, and then, a numerical model was validated using the advanced nonlinear dynamic analysis software Extreme Loading for Structures. The system was capable of developing large deformations associated with catenary response in the beams without failure of the connections. The beam ultimate rotation is larger than the deformation limit given in the codes.